Daybreak of freedom : the Montgomery bus boycott - Burns, Stewart (Civil rights and social justice., 1997)
"The Montgomery bus boycott was a formative moment in twentieth-century history: a harbinger of the African American freedom movement, a springboard for the leadership of Martin Luther King Jr., and a crucial step in the struggle to realize the American dream of liberty and equality for all. In Daybreak of Freedom, Stewart Burns presents a groundbreaking documentary history of the boycott. Using an extraordinary array of more than one hundred original documents, he crafts a compelling and comprehensive account of this celebrated year-long protest of racial segregation."--Jacket